PERAN KELOMPOK TANI (KTHKm) DALAM PENGELOLAAN HUTAN KEMASYARAKATAN DI DESA KARANGASEM, KECAMATAN PALIYAN, GUNUNGKIDUL, DAERAH ISTIMEWA YOGYAKARTA - , Restu Widhastri, Prof. Ir. Sudaryono, M.Eng.Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
A rapid deforestation of the state forest in Gunungkidul has began since 1997, included one in Karangasem village, Paliyan, Gunungkidul. The rehabilitation through the Community Forest program serves as the solution for the forest problems by giving trust to the local community to develop the forest in accordance to their need, abilities and knowledge. This research explores the roles of the Community Forest Farmer Group (KTHKm) in the management of the Community Forest in Karangasem village, Paliyan, Gunungkidul. Data were acquired through in-depth interviews involving informants chosen with purposive and snowball sampling method. The analysis is done using qualitative inductive with phenomenological approach. This research found that the Community Forest program is a multistakeholder program involving various element of the community in which the community itself acted as the main player. The KTHKm played a role as catalyst for the integration between the community empowerment and forest rehabilitation. KTHKm role as a catalyst in the rehabilitation of the forest is to build agreement among groups in the community, organized the activities in order to improve the quality of the environment, and kept the security of the forest. Its role as a catalyst for community empowerment is to improve the prosperity and the independence of the community.